Symmetry Analysis of the Discrete Nonlinear Boundary Value Problems for the Wave Equation - Yildirim, Ozgur; Caglak, Sumeyra (AMER INST PHYSICS, 2019)
Lie point symmetries of the discrete boundary value problem for sine-Gordon equation are determined. The symmetry preserving difference scheme corresponding to the boundary value problem (BVPs) for sine-Gordon equation is studied.
Keywords: Lie symmetry analysis; Partial difference equations; Boundary value problems; LIE; Mathematics; Physics